Pengaruh Pelayanan Sistem Online dan Promosi Terhadap Keputusan Pembelian Tiket Kereta Api Ekonomi (Study Kasus pada Penumpang Kereta Api Ekonomi di Stasiun Lahat) - Tri Rusilawati Kasisariah; Hayani Hayani; Hestin Hestin (Indo Publishing, 2026)
This study aims to examine the effect of the online service system and promotion on the purchasing decisions of economy-class train tickets at Lahat Railway Station. The study involved 100 respondents, with data collected through questionnaires and analyzed using multiple linear regression with SPSS (Statistical Package for the Social Sciences) version 22 for Windows 32-bit. The results indicate that the online service system and promotion simultaneously have a significant effect on purchasing decisions, as reflected in the regression equation Y = 22.273 + 0.122X₁ + 0.373X₂, indicating that when the online service system and promotion variables are equal to zero, the purchasing decision score is 22.273. The t-test results reveal that the online service system does not have a significant effect on the purchasing decisions of economy-class train tickets at Lahat Railway Station, whereas promotion has a significant positive effect. Furthermore, the F-test demonstrates that the online service system and promotion jointly have a significant influence on the purchasing decisions of economy-class train tickets in South Sumatra.